Consulting report – CICLO - Federschmid, Laura; Nashman, Rachel Anfrea; Chang Chumpitaz, Renato Manuel (Pontificia Universidad Católica del Perú, 2023)
El proyecto de Eco Adoquines de la empresa CICLO es una ambiciosa iniciativa que busca aumentar su capacidad y participación en el mercado a través de la inversión en activos fijos y capital de trabajo. Para respaldar esta estrategia, se han realizado exhaustivos estudios cualitativos y cuantitativos que revelan un Return on Invested Capital (ROIC) actual del 10.57%. El plan de negocios se enfoca en el análisis de mercado, la estrategia de negocios y el pronóstico financiero para impulsar las ventas y mejorar la posición de Ciclo en el mercado. Con el objetivo de aumentar su participación de mercado del 0.35% actual al 5% para finales de 2027, Ciclo planea la contratación de tres especialistas en finanzas, operaciones y marketing. Estos expertos serán clave para ordenar las finanzas, desarrollar estrategias de gestión de recursos y marketing, y mejorar la competitividad de la empresa en el mercado. Se proyecta que el proyecto de Eco Adoquines generará un Valor Neto Actual de S/ 412,250.88, una Tasa Interna de Retorno del 52%, y un retorno de inversión en 2 años, 3 meses y 4 días, lo que demuestra el atractivo potencial de inversión en esta iniciativa. En resumen, CICLO se embarca en un proyecto estratégico para expandir su presencia en el mercado a través de Eco Adoquines. Con un enfoque claro en el análisis, la estrategia y la inversión en recursos clave, la empresa busca un crecimiento sostenible y rentable, respaldado por sólidos indicadores financieros y un retorno de inversión atractivo.

CICLO is a sustainable construction company founded in 2015, with operations commencing in 2020, focusing on the production of eco pavers made from recycled construction material. The company operates in two main lines of business: (1) collecting construction waste, and (2) converting the collected material into construction material. Despite the significant environmental benefits and market potential of its operations, CICLO faces a critical challenge of insufficient funding which hampers its growth and scalability. To address this, the company aims to develop a comprehensive business plan to present to potential investors to secure the necessary funding. The business plan is structured into three main categories: market analysis, financial information, and growth strategy. The financial information will include detailed financial statements, projections, and a break-even analysis to provide a clear picture of the company’s financial health and future prospects. The market analysis will provide an overview of the current market scenario, including the demand for sustainable construction materials, competitor analysis, and the potential market share that CICLO can capture. The growth strategy will outline the company's plan for scaling its operations, expanding its product line, and capturing a larger market share. Qualitative and quantitative data will be utilized to analyze the company thoroughly and present a compelling case for investment. The analysis will not only demonstrate the financial viability of CICLO but also highlight the environmental impact of its operations, aligning with the growing trend of impact investing. Implementing recommendations for the company moving forward will also be included, ensuring the long-term success and sustainability of the business. By securing the necessary funding, CICLO aims to scale its operations, contribute to a more sustainable construction industry, and provide a lucrative return on investment for its stakeholders. The business plan will serve as a roadmap for achieving these objectives and a tool for convincing potential investors of the compelling opportunity that CICLO represents.
Keywords: Consultores de empresas--Planificación estratégica; Pavimentos--Aspectos ambientales; https://purl.org/pe-repo/ocde/ford#5.02.04